Hubungan Pengetahuan dengan Faktor Resiko Terjadinya Hiv/AIDS pada Siswa/i SMP PGRI 13 Kota Bogor Tahun 2023 - Fauziah, Nurul Azmi; P, Abdya Andirni C; Putri, Angelika (STIKES Ngesti Waluyo, 2024)
Human Immunodeficiency Virus (HIV) infection is a decrease in immunity caused by the HIV virus that can attack humans, making individuals susceptible to various infections and diseases. The continuation of HIV infection is Acquired Immunodeficiency Syndrome (AIDS). HIV infection is greatly influenced by individual behavior, especially related to sexual behavior and narcotic use. This research aims to determine the relationship between HIV/AIDS knowledge and risk factors for the occurrence of HIV/AIDS in students at PGRI 13 Middle School, Bogor City. An analytical survey with a cross-sectional approach was applied in this research. All 40 students of class VII and VIII of SMP PGRI 13 in the Sindangbarang area constitute the population in this study. The sample for this research was determined using Simple Random Sampling, totalling 36 people. The results of the study showed that there was no relationship between age, gender, education, and knowledge of HIV/AIDS. Additionally, there is a relationship between attitudes and knowledge of HIV/AIDS.